Production, purification and identification of Glycine,N-(m-anisoyl)-methyl ester from Pseudomonas aeruginosa with antimicrobial and anticancer activities. - Sawsan Abd Ellatif; Nermine N. Abed; Amira Y. Mahfouz; Enayat M. Desouky; Dalia K. Abd El Hamid (Kuwait Journal of Science)
The present research is a trial to extract antimicrobial and anticancer substance(s) from Pseudomonas aeruginosa. The bacterial isolate S1B20 exhibited the highest antimicrobial activity and is identified on the basis of 16S rRNA gene sequence as Pseudomonas aeruginosa MG429777. Extraction of various antimicrobial substance(s) (both proteinous and non-proteinous substances) were carried out. About applying the extract of antimicrobial substances from Pseudomonas aeruginosa MG 429777, chloroform established to be the strongest solvent for extraction of the antimicrobial substance, while 60% ammonium sulfate saturation stage was the brightest to obtain active bacteriocin fraction. The molecular weight of the refined bacteriocins estimated as 124 kDa. Quantitative results of GC-mass spectral analysis and IR spectroscopy of nonproteinaceous and proteinous antimicrobial agent delivered by Pseudomonas aeruginosa MG429777 was Oxime methoxy phenyl and Glycine, N-(m-anisoyl)-methyl ester. The research concern mainly on the application of  Glycine, N-(m-anisoyl)-methyl ester that proved to have a distinct antibacterial and antitumor force against three carcinoma cell lines.